Femoral hernia with vermiform appendix herniation: a case report and review of the literature - Papatheofani, Vasiliki (J Surg Case Rep, 2021)
Femoral hernias constitute 2–4% of all groin hernia repairs. Herniation of the vermiform appendix into the femoral hernia sac is rare. The majority of patients with appendix hernias are asymptomatic and diagnosis is made intraoperatively. We report about a case of a female patient presenting with an irreducible right-sided femoral hernia without symptoms.